Low–lying states of odd nuclei in the south–west 204Pb region - Sharrad, Fadhil (Publishing House of the Romanian Academy, 2013)
Binding energy of the ground state, energy levels and the B(E2) values of both positive and negative parities for 203,205Au, 203,205Hg, 203-207Tl and 203-207Pb isotopes have been calculated through shell model calculations using the shell model code OXBASH for Windows by employing the Modified Kuo-Herling interaction (khhe) for neutron and proton hole orbits in 208Pb. The binding energy calculations were in good agreement with experimental data. The predicted low-lying levels (energies, spins and parities) and B(E2) values results were reasonably consistent with the available experimental data.